Village Government Strategy in Community Economic Empowerment through Village-Owned Enterprise Program - Sastika, Halifah Anggun; Aini Mayasiana, Nur (Indonesian Journal Publisher, 2024)
The Village-Owned Enterprise program is expected to have a positive impact in boosting the village economy. Therefore, a mature strategy is needed from the Village Government through the Village-Owned Enterprises program to identify and utilize local potential in the village. This study aims to examine the strategies implemented by the Wonoasri Village Government in an effort to empower the community's economy through the Dana Asri Sejahtera Village-Owned Enterprise program, as well as identify factors that support and hinder the implementation of these strategies. This research adopts the concept of Wheelen and Hunger's theory of strategy implementation, which consists of Programs, Budgets, and Procedures.The method applied in this research is descriptive qualitative method. In this study, the technique of determining informants was carried out by applying the snowball sampling method. The data collection techniques are through the stages of observation, interviews and documentation. Then the data is analyzed using the Miles and Huberman model theory. The results of this study indicate that the implementation of community economic empowerment strategies carried out by the Wonoasri Village Government through the Dana Asri Sejahtera Village-Owned Enterprise program is realized through the development of 3 types of business fields, namely 1) savings and loan business, 2) culinary market business, 3) livestock business. The strategy of the Wonoasri Village Government through the Dana Asri Sejahtera Village-Owned Enterprise program has run optimally due to supporting factors such as adequate capital and infrastructure. However, there are limited human resources that become obstacles in the implementation of strategies carried out by the Wonoasri Village Government through the Dana Asri Sejahtera Village-Owned Enterprise.